Influence of motivation and a new digitized training program on undergraduate dental students during preclinical scaling training - Miriam Seidel; Simone Sutor; Jonas Conrad; Anne Sophie Engel; Antje Geiken; Sonja Sälzer; Christian Graetz (BMC, 2020)
Abstract Background The current study evaluated whether a new digitized scaling training program (DTP: n = 30; supervisor-student-ratio 1:10) improves the performance of undergraduate dental student during a preclinical course in regard to two different instruments [sonic scalers (AIR) and Gracey curettes (GRA)] compared to a conventional training program (CTP: n = 19; supervisor-student-ratio 1:4). Methods All the participants received a two-hour lecture on both instruments, followed by a 12-week period with a weekly training program lasting 45 min (10 sessions); one group was supported by DTP. At the end of the training phase, all the participants performed the subgingival scaling of six equivalent test teeth using GRA and AIR. Treatment time, proportion of removed simulated biofilm (relative cleaning efficacy, RCE-b) and hard deposits (RCE-d) were recorded. By using a pseudonymized questionnaire with a 5-point Likert scale, self-assessment of scaling effort, handling, root surface roughness/destruction and effectiveness were evaluated. In addition, personal data such as age, gender, handedness, regularity of playing computer games/consoles and previous dental/technical or medical education were elevated and correlated with cleaning efficacy. Results The DTP participants showed higher effectiveness in RCE-b compared to those who used the CTP with GRA (71.54% vs. 67.23%, p = 0.004) and AIR (71.75% vs. 62.63%, p ≤ 0.001), and the DTP students were faster with both instruments (p ≤ 0.001). For RCE-d, there was no significant difference between the DTP and CTP groups (GRA p = 0.471; AIR p = 0.158), whereas DTP showed better RCE-d results with GRA versus AIR (84.68% vs. 77.85%, p < 0.001). According to the questionnaire, no significant differences were detected between the training groups in terms of self-assessment, handling, treatment time, root surface roughness/destruction or effectiveness of the instruments. The CTP group favored AIR compared to GRA regarding the fatigue effect. The CTP and playing computer games/consoles regularly was correlated with lower RCE-b, whereas previous education in medicine/dentistry was correlated with higher RCE-b values. Conclusions Within the limitations of the study, the DTP with a reduced supervision effort compared to the CTP resulted in higher effectiveness and lower instrumentation time for removing simulated biofilms.